Aprendizagem na Educação Física escolar: fundamentos da pedagogia da corporeidade - Soares, Leys Eduardo dos Santos (2022)
The Pedagogy of Corporeity (PC) is a teaching and research method that provides theoretical and methodological subsidies for the development of learning in School Physical Education. With the CP and its inspiration in the philosophy of C. S. Peirce, we aim to insert in School Physical Education the debate of the semiotic problem of learning, because learning is treated as semiosis, action of signs in the circumstance, producing existential effects. The PC considers that School Physical Education is capable of generating new ways of interacting with the world, through the continuous change of habits, reconfiguring the ways of being and acting. Therefore, our work had the following research problem: what are the implications of the conception of learning from the Pedagogy of Corporeity for School Physical Education? To answer this question, we conducted a conceptual research that had two stages: 1 - Conceptual Overview: it consisted of a survey of the CP texts (totaling 378 examined pages) and the selection of concepts; 2 - Conceptual Elaboration: the theses of CP learning were identified and the theses were examined, using as analysis criteria: the degree of originality, the evaluation of each thesis' applicability, and their possible theoretical-methodological contributions to the area. An original thesis was outlined, discussing the "sub-thesis" formulations that derived from it, representing the path of the learning experience in Physical Education. Knowing develops in a learning situation, where the game is the pivot. And the occurrence of these situations is capable of self-generating a learning environment, a communication zone, whose flow of information mobilizes the learner to "tune", "translate", and "subjectify". The learning product is a singular configuration, a way to interact in the circumstance more efficiently. After analytical comparison, we conclude that the thesis and the "subthesis" of learning through PC, by including the emotional, the energetic and the logical, overcome dichotomies of focus and broaden the theoretical and methodological scope in dealing with learning in School Physical Education.